Limiting the Authority of Incumbents and State Officials in Presidential Election Campaigns: Pembatasan Wewenang Petahana dan Pejabat Negara dalam Kampanye Pemilihan Umum Presiden - Mochamad Adli Wafi; Deka Oktaviana (Universitas Islam Indonesia, 2024)
This article examines the problems and reconstruction of campaign regulations for incumbents and state officials in the Presidential and Vice-Presidential Elections. In this study, there are three formulations of the problem raised. First, how are the problems of campaign regulations by incumbents and state officials in the presidential election in Law No. 7 of 2017 on General Elections (Election Law). Second, how is the interpretation of the Constitutional Court regarding the regulation of general election campaigns carried out by incumbents and state officials? Third, how is the reconstruction of campaign regulations for incumbents and state officials to prevent potential abuse of power. The research method used in this article is normative juridical, with secondary data analysis using a statutory approach and a conceptual approach. This article concludes that there are legal imperfections (lex imperfecta) that stem from three problems: 1) provisions on leave for incumbents who wish to run again; 2) provisions on resignation for state officials who wish to run; and 3) provisions on leave for state officials who wish to campaign. Furthermore, the Author found that there has been no testing of the Election Law that questions the limitation of authority for incumbents and state officials in the election campaign so the interpretation of the Constitutional Court has not been found in this aspect. To overcome those problems, the Author formulated several formulations of campaign regulations for incumbents and state officials, including: 1) regulations on leave for the incumbent president and/or vice president who intend to run for office; 2) regulations on state officials who intend to run for office; 3) regulations on leave for state officials who participate in the campaign; and 4) strict administrative sanctions in enforcing restrictions.Keywords: Campaign, Abuse of Authority, Incumbent, and State Official Abstrak. Artikel ini mengkaji problematika dan rekonstruksi pengaturan kampanye bagi petahana dan pejabat negara dalam pemilihan umum presiden dan wakil presiden. Dalam penelitian ini, terdapat tiga rumusan masalah, yakni: Pertama, bagaimana problematika pengaturan kampanye oleh petahana dan pejabat negara dalam pemilihan presiden pada Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum (UU Pemilu); Kedua, bagaimana penafsiran Mahkamah Konstitusi mengenai pengaturan kampanye pemilihan umum yang dilakukan oleh petahana dan pejabat negara; dan Ketiga, bagaimana rekonstruksi pengaturan kampanye petahana dan pejabat negara guna mencegah potensi penyalahgunaan kekuasaan. Metode penelitian yang digunakan adalah yuridis normatif, dengan analisis data sekunder menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Artikel ini menyimpulkan bahwa terdapat ketidaksempurnaan hukum (lex imperfecta) yang berhulu pada tiga problematika: 1) ketentuan cuti bagi petahana yang hendak kembali mencalonkan diri; 2) ketentuan pengunduran diri bagi pejabat negara yang ingin mencalonkan diri; dan 3) ketentuan cuti bagi pejabat negara yang ingin berkampanye. Lebih lanjut, Penulis menemukan bahwa belum terdapat pengujian pada UU Pemilu yang mempersoalkan pembatasan wewenang bagi petahana dan pejabat negara dalam kampanye Pemilu, sehingga penafsiran Mahkamah Konstitusi belum ditemui pada aspek ini. Untuk mengatasi problematika-problematika a quo, Penulis merumuskan beberapa formulasi pengaturan kampanye bagi petahana dan pejabat negara, mencakup: 1) pengaturan cuti bagi presiden dan/atau wakil presiden petahana yang hendak mencalonkan diri; 2) pengaturan pejabat negara yang hendak mencalonkan diri; 3) pengaturan cuti bagi pejabat negara yang ikut serta kampanye; dan 4) sanksi administrasi yang tegas dalam menegakkan pembatasan.Kata Kunci: Kampanye, Penyalahgunaan Wewenang, Petahana, dan Pejabat Negara